2016
DOI: 10.21767/2476-1974.100025
|View full text |Cite
|
Sign up to set email alerts
|

Lumpy Skin Disease

Abstract: Lumpy skin disease (LSD) is an infectious, eruptive, occasionally fatal disease of cattle caused by a virus of the family Poxviridae (genus Capripox), which is sometimes also termed as Neethling virus. LSD does not have a high fatality rate, usually less than 10%. LSD has an economical importance because of permanent damage to hides, the prolonged debilitating effect especially in severely affected animals with consequent losses resulting from reduced weight gain, temporary or permanent cessation of milk produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…Although the pathogenesis and exact etiology of immune-mediated vasculitis is unknown, advances in molecular research have revealed that an imbalance in inflammatory cytokines is central to the pathogenesis of this condition [32]. Our results were also supported by Abdulqa et al [33], who reported that the virus might infect different types of cells, including pericytes, fibroblasts, epithelial, and endothelial cells. Infected areas developed extreme vasculitis and lymphangitis because of viral replication in pericytes, endothelial cells, and possibly some cells in blood vessels and lymph vessel walls.…”
Section: Discussionsupporting
confidence: 87%
“…Although the pathogenesis and exact etiology of immune-mediated vasculitis is unknown, advances in molecular research have revealed that an imbalance in inflammatory cytokines is central to the pathogenesis of this condition [32]. Our results were also supported by Abdulqa et al [33], who reported that the virus might infect different types of cells, including pericytes, fibroblasts, epithelial, and endothelial cells. Infected areas developed extreme vasculitis and lymphangitis because of viral replication in pericytes, endothelial cells, and possibly some cells in blood vessels and lymph vessel walls.…”
Section: Discussionsupporting
confidence: 87%
“…LSD signs can be the subclinical or clinical and include fever, skin nodules that cover the entire animal’s body, and edema of the limbs and brisket with lameness and enlarged of the superficial lymph node in few animals [6]. LSDV is transmitted through direct contact between infected and noninfected animals, indirect mechanical and biological transmission by Aedes aegypti mosquitoes, Culicoides , and hard Ixodid ticks that are associated with wet, warm summer seasons have been reported [7,8]. Cattle of all breeds, including wild ruminants, are susceptible [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the disease that first reported in 1929 in Zambia is suspected to be resulted by either poisoning or hypersensitivity to an insect bite, until the infectious nature was recognized in 1943 [2,3]. Since then, LSD is spread to other southern and northern countries of Africa, and the Middle East incurred enormous economic losses in cattle livestock [4]. In Iraq, the first infected foci of LSD were indicated in many regions of Nineveh and Baghdad Provinces in 2013 [5].…”
Section: Introductionmentioning
confidence: 99%